Tackling Excessive Waiting Times for Elective Surgery A Comparison of Policies in Twelve OECD Countries - Hurst, Jeremy (OECD Health Working Papers, 2003)
Waiting times for elective (non-urgent) surgery are a main health policy concern in approximately half of OECD countries. Mean waiting times for elective surgical procedures are above three months in several countries and maximum waiting times can stretch into years. They generate dissatisfaction for the patients and among the general public. Is there a solution? This report discusses the waiting-time phenomenon and provides a comparative analysis of policies to tackle waiting times across 12 OECD countries. At worst, waiting times can lead to deterioration in health, loss of utility and extra costs. However, one surprising result is that there is little evidence of health deterioration from a review of studies of patients waiting for a few months for different elective procedures across a range of countries. Moreover, such patients are quite tolerant of short and moderate waits, although the general public often expresses more concern about waiting. It is argued that there will be both ...